2015
DOI: 10.4314/ijbcs.v8i5.4
|View full text |Cite
|
Sign up to set email alerts
|

Effets des graines torréfiées de Vigna unguiculata (niébé) comme source de protéines, dans l’alimentation des poules locales en ponte au Burkina Faso, sur leurs performances zootechniques et la rentabilité économique des régimes

Abstract: L'étude avait pour but d'évaluer les effets de l'incorporation des graines torréfiées de niébé dans l'alimentation de la poule locale en ponte, sur ses performances zootechniques et économique. Six coqs et soixante poules de race locale de 7,5 mois d'âge ont été répartis en six lots, par tirage aléatoire. Deux régimes alimentaires aux mêmes contraintes nutritionnelles dont un témoin et un régime expérimental comportant 8% de graines torréfiées de niébé ont été préparés. La ponte, les caractéristiques des oeufs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
2
6
1
3
Order By: Relevance
“…It was found that the consumption index increases with the number of days of rearing (Table VI). This observation is con rmed by other authors such as BETENE(2006) and ZONGO (2016) The average cost (213.77 FCFA/Kg) of the formulas is lower than the cost (219.05 FCFA/Kg) of the feed formulated by Ouattara et al, (2015) and the price charged on the national market for poultry feed which varies between 240 and 300 FCFA/Kg (CPAVI ; Faso Grain, Kono Aliment ; Société de Fabrique d'Aliments pour Bétail) (Ouattara et al, 2015). This decrease can be explained by the rational use of raw materials in the formulation thanks to the design of experiments method.…”
Section: Discussionsupporting
confidence: 75%
“…It was found that the consumption index increases with the number of days of rearing (Table VI). This observation is con rmed by other authors such as BETENE(2006) and ZONGO (2016) The average cost (213.77 FCFA/Kg) of the formulas is lower than the cost (219.05 FCFA/Kg) of the feed formulated by Ouattara et al, (2015) and the price charged on the national market for poultry feed which varies between 240 and 300 FCFA/Kg (CPAVI ; Faso Grain, Kono Aliment ; Société de Fabrique d'Aliments pour Bétail) (Ouattara et al, 2015). This decrease can be explained by the rational use of raw materials in the formulation thanks to the design of experiments method.…”
Section: Discussionsupporting
confidence: 75%
“…Les feuilles, les gousses immatures et les graines sont consommées par les populations car très riches en protéines, en calcium, en fer et en l'acide nicotinique (Diouf, 2011). Le fourrage, les produits et sousproduits du niébé sont utilisés dans l'alimentation de certains animaux (Sana et al, 2020 ;Ouattara et al, 2014).…”
Section: Introductionunclassified
“…Cowpea (Vigna unguiculata) is an important grain legume crop in Sub-Saharan Africa. The crop is an excellent source of protein for both human and animal nutrition (Ouattara et al, 2014;Enyiukwu et al, 2018;Jayathilake et al, 2018). It also serves as a cash crop in the largest production areas (Horn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%